Western Balkans 2024 - Baker, Mark (Travel writer) (Lonely Planet guidebooks., 2024)
Lonely Planet's Western Balkans is our most comprehensive guide that extensively covers all the countries have to offer, with recommendations for both popular and lesser-known experiences. Glimpse breathtaking views of Dubrovnik: grab coffee in Budva's Old Town ;and trek the landscapes of Rugova Mountains; all with your trusted travel companion. Inside Lonely Planet's Western Balkans Travel Guide: Lonely Planet's Top Picks - a visually inspiring collection of the destination's best experiences and where to have them Itineraries help you build the ultimate trip based on your personal needs and interests Local insights give you a richer, more rewarding travel experience - whether it's history, people, music, landscapes, wildlife, politics Eating and drinking - get the most out of your gastronomic experience as we reveal the regional dishes and drinks you have to try Toolkit - all of the planning tools for solo travellers, LGBTQIA+ travellers, family travellers and accessible travel Colour maps and images throughout Language - essential phrases and language tips Insider tips to save time and money and get around like a local, avoiding crowds and trouble spots Covers Albania, Bosnia and Herzegovina, Croatia, Kosovo, Macedonia, Montenegro, Serbia, Slovenia and more!